Sure, I'll join your cult: a memoir of mental illness and the quest to belong anywhere (Simon & Schuster Audio, Gallery Books, 2023)
"From "weird, scary, ingenious" (The New York Times) stand-up comedian Maria Bamford, a brutally honest and hilariously frenetic memoir about show business, mental health, and the comfort of rigid belief systems--from Dale Carnegie's How to Win Friends and Influence People, to Suzuki violin training, to Richard Simmons, to 12-step programs. Maria Bamford is a comedian's comedian (an outsider among outsiders) and has forever fought to find a place to belong. From struggling with an eating disorder as a child of the 1980s, to navigating a career in the arts (and medical debt and psychiatric institutionalization), she has tried just about every method possible to not only be a part of the world, but to want to be a part of it. In Bamford's signature voice, Sure, I'll Join Your Cult, brings us on a quest to participate in something. With sincerity and transparency, she recounts every anonymous fellowship she has joined (including but not limited to: Debtors Anonymous, Sex and Love Addicts Anonymous, and Overeaters Anonymous), every hypomanic episode (from worrying about selling out under capitalism to enforcing union rules on her Netflix TV show set to protect her health), and every easy 1-to-3-step recipe for fudge in between. Singular and inimitable, Bamford's memoir explores what it means to keep going, and to be a member of society (or any group she's invited to) despite not being very good at it. In turn, she hopes to transform isolating experiences into comedy that will make you feel less alone (without turning into a cult following)"--